Efeito da salinidade e temperatura da água no desempenho hidráulico de fitas gotejadoras em condições laboratoriais - Cunha, Jorge Luiz de Oliveira (2017)
Drip irrigation system in the radiation area of the agricultural crop in order to provide that a partner of the soil is close to the field capacity. In this irrigation system as dripping tapes are exposed to physical-chemical and microbiological agents that increase the appearance of emitter obstruction, reducing the operational life cycle of the system that operate with water of inferior quality. The objective of this study was to study the variation of irrigation water temperature and salinity as factors that contribute to the process of obstruction of the tapes, reducing its useful life, control solution of flow rate uniformity of the emitters of the drip tapes under laboratory conditions. For this, an experimental bench was set up not Laboratory of Machine Instrumentation and Agricultural Mechanization of the Universidade Federal Rural do Semi-Árido, in Mossoró-RN; Where the experimental tests were carried out with three types of drip tapes operated under controlled conditions of temperature, water salinity and service pressure. The experimental bench has the following dimensions: 1,50m x 3,50m (width and length), height of 1,00 m and 1,20 m (low point and highest point respectively). On the same saw, fixed four fiber cement tiles in an area of 0.90 m x 3.00 m (width and length), with slope of 8% and at its base to insert a collecting trough connected to the ground water reservoir of 0.10m3. To allow a recirculation of the test water, a 1/4 hp centrifugal pump was used. Four lines of tapes with three meters of length were used in the workbench, which were submitted to short test cycles, established at 100, 250, 500 and 750 hours of operation and water temperature of 20 and 30ºC. To control the temperature of the water with the heating system with power of 2.00 kW and cooling of 7.04 kW. The electrical conductivity of water ranged from 0.52 dS m-1 to 2.56 dS m-1. After the end of each cycle of operation, samples of the tapes were collected for scanning electron microscopy of the holes and internal walls. The flow rate and the Distribution Uniformity Coefficient were used to monitor the hydraulic performance of the drip tapes. The results indicated that the increase of salinity of the irrigation water resulted in a decrease in the flow rate of the drip irrigation system, without causing a change in the classification of the Distribution Uniformity Coefficient. Water quality analyzes indicated a potential risk for soil sodification. The increase in temperature and salinity increased the formation of microorganisms and precipitates of calcium, resulting in increased frequency of maintenance in the system